2012
DOI: 10.1002/14651858.cd007512.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Techniques of flushing and reperfusion for liver transplantation

Abstract: There is currently no evidence to support or refute the use of any specific technique of flushing or reperfusion during liver transplantation. Due to the paucity of data, absence of evidence should not be confused with evidence of absence of any differences. Further well designed trials with low risk of systematic error and low risk of random errors are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…Some authors have suggested that minimization of organ manipulation, rapid aortic cannulation and cold perfusion, topical cooling, and rapid hepatectomy have protective effects for older liver grafts. 14 Another major concern regarding the use of old grafts is the potential increased rate of vascular and biliary complications due to underlying atherosclerosis of these donors. 14 Our findings indicate that the rate of retransplant due to hepatic artery thrombosis is not different in older donors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have suggested that minimization of organ manipulation, rapid aortic cannulation and cold perfusion, topical cooling, and rapid hepatectomy have protective effects for older liver grafts. 14 Another major concern regarding the use of old grafts is the potential increased rate of vascular and biliary complications due to underlying atherosclerosis of these donors. 14 Our findings indicate that the rate of retransplant due to hepatic artery thrombosis is not different in older donors.…”
Section: Discussionmentioning
confidence: 99%
“…14 Another major concern regarding the use of old grafts is the potential increased rate of vascular and biliary complications due to underlying atherosclerosis of these donors. 14 Our findings indicate that the rate of retransplant due to hepatic artery thrombosis is not different in older donors. Ghinolfi and associates had the same findings in their study.…”
Section: Discussionmentioning
confidence: 99%
“…The reviews [3,11] and case series [8,9] were excluded from the meta-analysis. In total, 11 studies could be included.…”
Section: Results Of the Literature Search And Meta-analysismentioning
confidence: 99%
“…The level of evidence in most of the studies is very low [11]. We aimed to investigate which reperfusion technique of the liver graft in deceased donor liver transplantation is the most widely used in transplant centres within ET, and performed a review and meta-analysis of available literature on the topic to analyse which reperfusion technique is the best in terms of patients' survival, number of retransplantations and amount of biliary complications.…”
Section: Introductionmentioning
confidence: 99%
“…Here some studies hint that the way and se- quence of reperfusion influence the rate of ITBL (Heidenhain et al 2006;Farid et al 2011). The Cochrane database analysis searched for comparisons that included initial hepatic artery flush versus initial portal vein flush or simultaneous flushing and different types of blood venting or use of perfusion fluid (Gurusamy et al 2012). There was no significant difference in mortality, graft survival, or severe morbidity rates in any of the comparisons.…”
Section: Liver Transplantation-techniquesmentioning
confidence: 99%